Socio-economic Impact of Foreign Employment and Remittance in Household Activities in Besishahar Municipality - Ale, Dambar Bahadur (Marsyangdi Journal, 2024)
Remittances from foreign employment have played an important role in the household economy in Nepal. This article aimed to explore the socio-economic impact of foreign employment and remittances on household activities in the Besishahar Municipality. Following the purposive sampling procedure, I selected 30 households for the cross-sectional survey and administered a questionnaire to collect data. In addition to this, 10 participants were selected for in-depth interviews to collect qualitative information. The findings of the study revealed that foreign employment has improved the socioeconomic condition of a family and brought changes in the source of income, children’s education, settlement process, and prestige and status of family members in society. I have suggested using the remittance in productive activities such as self-employment, financial investment, etc. rather than investing in unproductive sectors like building a house or purchasing land in urban areas. The findings of the study may be useful in policy making at the local and federal levels in Nepal as a large number of young people migrate every day for foreign employment abroad. Policymakers should be aware of the management of safe labour migratory flows both to the countries of origin and destination. Its implication can be an effective strategy for adaptation as it generates financial and human capital that contributes to the sustainable alleviation of poverty.